Managing Hybrid Learning with Large Groups during the COVID-19 Pandemic - Marija STEVKOVSKA (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2022)
This article aims to examine the effectiveness of hybrid learning with large groups. A cross-sectional study was conducted to answer the three research questions: 1) Is there a significant difference between the achievement of online and face-to-face students? 2) What are the main advantages and disadvantages of hybrid classes? and 3) What can be done to increase the effectiveness of hybrid classes? The research hypothesis is that there is a significant difference between the exam results. The mid-term and final exam results of both groups of students were compared through the independent and dependent t-test, which indicated there was no significant difference between the two groups.